Symptomatic pain relief of postherpetic neuralgia with 5% lidocaine patch treatment: a case series report - Nieto-Gutierrez, Wendy (2024)
Objective: To describe the effects of the 5% lidocaine patch on the symptomatic relief of Peruvian patients with postherpetic neuralgia. Methods: Case series report of adult patients with post-herpetic neuralgia admitted to and treated at the Air Force Central Hospital in Lima. Symptomatic relief was defined as the difference between the specified pain score before and after patch treatment. The pain score was evaluated by the visual analogue scale and the Pain Assessment in Advanced Dementia scale, for patients with dementia. Results: Twenty-two patients with postherpetic neuralgia (mean age 74.4 ± 12.40 years) were recruited, 17 of whom began topical therapy with lidocaine following oral systemic treatment. The main reasons for the decision to change were a persistent pain and the adverse effects of the preceding therapy. A statistically significant decrease in pain symptoms was observed after the use of the lidocaine patch (p<0.01), and no adverse reactions to the patch were reported during the follow-up period. Conclusions: A statistically significant pain reduction found after the use of topical treatment. New studies that overcome the limitations of this and others previously published, are suggested.